Study on robustness of rebound hammer and ultrasonic pulse velocity measurement in several concrete damage levels. Issue 1 (April 2021) - Kencanawati, N N; Akmaluddin,; Marlitasari, R; Paedullah, G
Abstract: The results of reading the rebound number in a hammer test and velocity in an ultrasonic pulse velocity (UPV) test are usually associated with concrete compressive strength. A correlation or regression is provided to convert those parameters. However, several factors can influence this correlation. One of them is the level of concrete damage. The purpose of this study is to look at the robustness of hammer and UPV reading data in various concrete damage conditions. Experiments were carried out by testing three groups of concrete strength: 25, 35, and 45 MPa. All the concrete was tested using the UPV and rebound hammer test. The damage was determined as concrete which has decreased compressive strength by 30% (low), 50% (medium), and 80% (high) of the initial strength. The initial strength was the maximum compressive strength on each concrete group which was determined by compression testing. The rebound hammer data shows the correlation results that are almost the same as the correlation provided by the manufactures for concrete without damage and slight damage. But this is not the case with medium and highly damaged concrete, showing the results of the highly distorted correlation. The greater the level of damage, the greater the deviation. For concrete which damage level up to 80%, there is a deviation ratio of up to 3.6 times compared to the correlation value provided by the tool. Furthermore, the reading of UPV has a constant correlation without being affected by damaged concrete conditions up to the velocity of 3500 m/s. Thus, in a rapid assessment of the strength and safety of existing concrete structures, the robustness of a hammer test implements in concrete with sound and slight damage, but for concrete with beyond of elastic damage conditions, it must be accompanied by other tools such as UPV or sampling core.